A Study on Implementation of National Rural Employment Guarantee Act for Social Security in India - Ganesh, Dr.M.P Suri; MADAPA, Mr. KARTEEK (IJRDO -Journal of Computer Science Engineering, 2015)
The National Rural Employment Guarantee Act (NREGA), enacted by the Government of India in 2005, is perhaps the most ambitious anti-poverty scheme launched anywhere in the world. However, the scheme has shown several anomalies when it comes to its implementation in the right manner. Some of the problems are discussed in our paper.